Women solo travellers: motivations and experiences - Pereira, Andreia (2018)
Introduction: The concept of female solo traveler, despite recent, has become a relevant tourist segment. As tourists, these women are looking for journeys that bring more than a trip from one place to another. They choose to go alone in the pursuit of adventure, independence, feeling of personal fulfillment, individuality and escape. They do not travel alone because they have no choice or because they are loners. They are driven by specific and consciousness motivations. Objective: In this conceptual work, a set of solo travel motivations are categorize based on literature review, to identify why women, choose to travel alone. The focus of this article is to explore the relationship between these motivations with women solo travel experiences providing a conceptual model. Methods: An extensive literature review focusing on the concept of tourism motivations and experiences provide a framework that allows assesses the specific motivations that driven women into travel alone and the corresponding solo traveler experience dimensions. The multi-dimension scales considers eight motivations dimensions: (1) escape, (2) self-identity and development, (3) challenge, (4) connectedness with others, (5) learning, (6) adventure, (7) new life perspectives, and (8) autonomy; and five experience dimensions: (1) sense, (2) feel, (3) think, (4) act, and (5) relate based on Schmitt’ model tourism experience (Schmitt, 1999). Results: Despite an extensive literature review, there are few studies based on experiences and motivations of women solo travelers. Conclusions: Even if it is a market that has not been very explored and studied has gained numerous supporters around the world, translating into an expressive impact not only in sociological terms, but also in its tourist experience.